If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+28)+(2x+27)=90
We move all terms to the left:
(3x+28)+(2x+27)-(90)=0
We get rid of parentheses
3x+2x+28+27-90=0
We add all the numbers together, and all the variables
5x-35=0
We move all terms containing x to the left, all other terms to the right
5x=35
x=35/5
x=7
| 3x^-2=7 | | 7(8+6x)=56 | | (7+y)(3y-2)=0 | | -2(-7x-5)=178 | | 5^2x-3=0.04 | | 3(1+1x)=3 | | x+6/7=-6/1/7 | | 7.92=g-5.61 | | -7(-10+5x)=0 | | -32=3.9g-8.6 | | H=W*Q*x | | x+5/7=-8/2/7 | | 2/9/n=10/45 | | 11m+7=29 | | -8m+3=67 | | k-4/2=-6 | | -3(-3x+5)-2(3-3x)=(-12+16x) | | x^2-100x+81=0 | | g/4−3=1 | | 3+-2u=-1 | | 1=2h−1 | | -5=1−3c | | X(.0825)+x=41 | | 10=5−c | | 10=5−-c | | k/2+4=5 | | k/2+ 4= 5 | | 2f+1=11 | | -5(3-4x)=-175 | | -7(6x-4)=-266 | | 1+2j=3 | | 6(-5-7m)=306 |